Making energy a priority - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The energy dimension by Christopher Hurst and Andrew Barnett 1990 172pp UKL9.95 ISBN 1 85339 074 7 Intermediate Technology 103/105 Southampton Row London WC1B 4HH, UK